Continental reckoning : the American West in the age of expansion - West, Elliott, 1945- (History of the American West., 2023)
"Elliott West lays out the main events and developments that together describe and explain the emergence of the American West and situates the birth of the West in the broader narrative of American history between 1848 and 1880"--